Who are they? Making non-traditional students visible - Gonçalves, Teresa (2014)
The implementation of the Bologna processes in Portugal allowed a national Law to be changed so that the access to Higher Education was made easier for mature students older than 23, who have some sort of professional experience. In this paper we’ll report the first (still superficial) results of a research project which, involving the universities of Aveiro and Algarve5, aims to study deeply non-traditional student’s situation in order to create conditions for improving their academic success and reduce dropout.